(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2023)
Adults who wish to continue their education often face numerous barriers, such as lack of time, lack of funding, lack of family support, lack of access to education, and lack of confidence in their academic abilities. To overcome these barriers, adults can consider flexible options, such as online education and seeking scholarships or financial aid programs. In addition, seeking support from friends and family can provide the motivation and encouragement needed to succeed. Perseverance and determination are also essential to overcoming barriers and achieving educational goals